Собачье сердце: роман, повести, рассказы / М. А. Булгаков - Булгаков Михаил Афанасьевич (Русская классика ХХ век, 2003)
Экземпляры: (20180205) / Инвентарный номер: 29168 / Цена: 72.82 / Сис.шифр: Р2 / Авт.знак: Б 90 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6